“SISTEMA DE ORGANIZACIONES POLÍTICAS EN EL ECUADOR: REGULACIÓN DE CANDIDATURAS Y ESTABILIDAD DE LA DEMOCRACIA” - Jimenez Obando, Jessica Magaly (2021)
The present academic dissertation degree is entitled “Political Organization System: Nomination of Candidates and Stability of Democracy”. This topic arose from the analysis made in a previous way, about Ecuador national elections and the high number of candidates that were accepted to participate in the election campaign. The problem emerges from facts related to representative democracy, focused on political organizations increase, this problem can be corroborated since the conceptual, doctrinaire and legal study, this allowed to evidence irregularities in the nomination of candidates, lack of control on the organization structure and the deficient requirements established on the law. On the last years it has been evident that political organizations have increased, in the way that in some experts’ opinion this fact is carrying Ecuador to a total breakdown in the democratic system, which has leave economic, social and legal consequences. Additionally, materials and methods have been applied in order to develop the investigation, furthermore surveys and interviews were employed to experts in electoral matter. To remedy this problem, some possible solutions has been analyzed too, in order to stop the excessive increase of political organizations, through the establishment of a legal reform project to the Ecuadorian democracy law, Ley Orgánica Electoral, Código de la Democracia, in order to increase the percentual number of requirements to conform political organizations and as well to the nominations of candidates. Rigorous control of the requirements, based on philosophical, political and ideological principles to guarantee a political organization system with democratic internal policy and a National Stability of Democracy.